Pengaruh Sosialisasi Pajak Bumi dan Bangunan (PBB) Terhadap Peningkatan Kesadaran Masyarakat Wajib Pajak Di Kecamatan Tempe Kabupaten Wajo - Muhammad Justiawal; Asmanurhidayani Asmanurhidayani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The importance of public awareness in paying land and building taxes (PBB) for state revenues and increasing regional finances. To achieve the intended goal, the government is carrying out various kinds of efforts, one of the efforts made by the government is by socializing how to increase public awareness so that they are active in paying taxes to increase regional income.